Cowden syndrome diagnosed by Lhermitte–Duclos disease - Yuan-Shao Chen; Yoon Bin Chong; Chih-Hung Lin; Ann-Shung Lieu (Formosan Journal of Surgery, 2019)
Cowden syndrome (CS) is a rare genetic disease which puts patients at an increased risk of developing mucocutaneous lesion, multiple hamartomas, breast cancer, thyroid cancer, and Lhermitte–Duclos disease (LDD). This article reviews the role of LDD in the diagnosis of CS. It is important for all clinicians to identify these patients due to the high risk of other associated malignancies.